2022
DOI: 10.3389/fpsyg.2022.939576
|View full text |Cite
|
Sign up to set email alerts
|

Chinese international students’ conceptualizations of wellbeing: A prototype analysis

Abstract: Wellbeing can mean different things to different people, even in the same culture with the same language. People living at the intersection of two languages and cultures, such as Chinese students studying in an English-speaking nation, not only speak a different language than their host country, but also may have different conceptualizations of wellbeing itself. This study investigated Chinese international students’ (aged 18–39, N = 123) conceptualizations of wellbeing using a modified prototype analysis, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The current study extends Huang et al (2020) and Huang et al (2022), with a specific focus on qualitative data collected from a sub-set of participants (Chinese international students in several universities across Australia). Interviews conducted by the first author between September 2019 and February 2020, and all procedures were approved by the [blinded for review] ethics review board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study extends Huang et al (2020) and Huang et al (2022), with a specific focus on qualitative data collected from a sub-set of participants (Chinese international students in several universities across Australia). Interviews conducted by the first author between September 2019 and February 2020, and all procedures were approved by the [blinded for review] ethics review board.…”
Section: Methodsmentioning
confidence: 99%
“…While these studies paint a concerning picture, few studies have focused on positive aspects of mental health, including students' experiences of wellbeing and aspects that effectively support wellbeing. Using a prototype analysis design, Huang, Kern, and Oades (2022) explored Chinese international students' conceptualisations of wellbeing, finding that wellbeing concepts were prototypically structured, with relationships, security, positivity/ optimism, physical health, and self-strength identified as key components to their wellbeing conceptualisations. In a mixed methods study exploring how Chinese international students understand wellbeing, Huang et al (2020) identified mental and physical health, security, relationship support, and prosperity as key themes.…”
Section: Chinese International Students In Australiamentioning
confidence: 99%
“…A further needed change is to integrate cultural, political, and particularly student lay conceptions of well-being and flourishing into schools’ efforts to promote well-being and flourishing. Asking students, parents, and teachers what well-being means to them, in their school and cultural context, is likely to increase understanding and collective ownership of well-being-related aspirations and changes (Huang et al, 2022).…”
Section: How Schools and Educators Should Promote Well-beingmentioning
confidence: 99%
“…The problem of social programme effectiveness leads to this submission's utilitarian goal, i.e., identifying countries with the most effective socio-economic policy. One may expect that in countries with the most effective socio-economic policy, the most significant increases in the indicators of the subjective well-being of households will occur [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%